2021
DOI: 10.1021/acsomega.0c06050
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Aspects of the Synthesized Pyrazoline Derivatives for AP1 5L X60 Steel Protection Against MIC and Acidization: Electrochemical, In Silico, and SRB Insights

Abstract: The inhibitory impact of low-cost synthesized pyrazoline derivatives named Pz series ( Pz1 and Pz2 ) on the corrosion of API 5L X60 carbon steel in 5 M HCl was inspected to serve as corrosion inhibitors against such a solution for its usage in the oilfield well acidization process. Also, the same compounds were unitized as biocides for sulfate-reducing bacteria (SRBs) to inhibit the microbial-induced corrosion effect. This study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Figure 1S2,S3 shows that the open potential values of carbon steel were in the negative direction after adding S2 and S3, which confirms that the damping effect of the compounds S1 and S2 is greater on the anodic reaction than on the cathodic reaction. 22,23 2.2. Potentiodynamic Polarization (PDP).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1S2,S3 shows that the open potential values of carbon steel were in the negative direction after adding S2 and S3, which confirms that the damping effect of the compounds S1 and S2 is greater on the anodic reaction than on the cathodic reaction. 22,23 2.2. Potentiodynamic Polarization (PDP).…”
Section: Resultsmentioning
confidence: 99%
“…According to the analysis of the Nyquist plot, it is a capacitive arc in the high-frequency region, which can come from not only the charge transfer resistance but also the electric double-layer capacitor. , It can be clearly observed that the capacitive loop radius continuously increases with the increase in SLLE concentration, showing that the corrosion of copper in sulfuric acid solution is due to the electrochemical reaction controlled by the charge transfer step, indicating that the corrosion reaction of Cu in H 2 SO 4 solution at this time is an electrochemical reaction controlled by the charge transfer step. It can also show that the rate of electrochemical reactions of Cu in 0.5 mol·L –1 H 2 SO 4 solution is slowed down and suppressed with SLLE added.…”
Section: Resultsmentioning
confidence: 98%
“…It is worth mentioning that the inhibition performance if inhibitor tends to increase with low η values. This is also reflecting the high reactivity and inhibition performance of the α-pinene moiety. , Another important descriptor is the ability of molecules to donate electrons to the Cu surface (Δ N Cu(111) ). A high and positive value of Δ N demonstrates that the great capacity of investigated ingredients to donate e- to the cooper surface, especially, the α-pinene molecule.…”
Section: Discussion and The Results Of The Studymentioning
confidence: 99%
“…A high and positive value of Δ N demonstrates that the great capacity of investigated ingredients to donate e- to the cooper surface, especially, the α-pinene molecule. We did not consider the effect of the dipole moments trend μ, on the inhibition performance because there is disagreement on its impact. …”
Section: Discussion and The Results Of The Studymentioning
confidence: 99%